Adhesives technology handbook - Ebnesajjad, Sina; Lanck, Arthur H. (William Andrew, an imprint of Elsevier, 2014)
Covering a wide range of industrial applications across sectors including medical applications, automotive/aerospace, packaging, electronics, and consumer goods, this book provides a complete guide to the selection of adhesives, methods of use, industrial applications, and the fundamentals of adhesion. Dr Ebnesajjad examines the selection of adhesives and adhesion methods and challenges for all major groups of substrate including plastics (thermosets and thermoplastics), elastomers, metals, ceramics and composite materials. His practical guidance covers joint design and durability, application methods, test methods and troubleshooting techniques. The science and technology of adhesion, and the principles of adhesive bonding are explained in a way that enhances the reader's understanding of the fundamentals that underpin the successful use and design of adhesives. The third edition has been updated throughout to include recent developments in the industry, with new sections covering technological advances such as nanotechnology, micro adhesion systems, and the replacement of toxic chromate technology